The past stuck in the present: historical turism and past spectacle of the jesuits of Rio Grande do Sul (Tempo e Argumento, 2009)
The article approaches the historical tourism and the uses of the past in the area of the missions of Rio Grande do Sul as propulsion force for the regional development. The past missionary and the ruins of the reductions are used by the agents of the tourism to attract visitors from Brazil and of the exterior. Several sites and tourist pamphlets publish the area and they promise to the tourists the opportunity of a displacement in the time and of a contact with the history, that one find preserved in the monuments and in the inhabitants' habits. Exploring the different modalities of tourism – ecological tourism, rural tourism and religious tourism - the agents and institutions involved with the promotion of the area they reinvent the past in agreement with demands of the present.
Keywords: historical tourism; Jesuit missions; past-show; present time